Retinal Injury Following Laser Pointer Exposure: A Systematic Review and Case Series - Birtel, Johannes (Dtsch Arztebl Int, 2017)
BACKGROUND: Recent years have seen a marked increase in laser-pointer-related injuries, which sometimes involve severe retinal damage and irreversible visual impairment. These injuries are often caused by untested or incorrectly classified devices that are freely available over the Internet. METHODS: We reviewed pertinent publications retrieved by a systematic search in the PubMed and Web of Science databases and present our own series of clinical cases. RESULTS: We identified 48 publications describing a total of 111 patients in whom both acute and permanent damage due to laser pointers was documented. The spectrum of damage ranged from focal photoreceptor defects to macular foramina and retinal hemorrhages associated with loss of visual acuity and central scotoma. On initial presentation, the best corrected visual acuity (BCVA) was less than 20/40 (Snellen equivalent) in 55% of the affected eyes and 20/20 or better in 9% of the affected eyes. Treatment options after laser-pointer-induced ocular trauma are limited. Macular foramina and extensive hemorrhages can be treated surgically. In our series of 7 cases, we documented impaired visual acuity, central visual field defects, circumscribed and sometimes complex changes of retinal reflectivity, and intraretinal fluid. Over time, visual acuity tended to improve, and scotoma subjectively decreased in size. CONCLUSION: Laser pointers can cause persistent retinal damage and visual impairment. In view of the practically unimpeded access to laser pointers (even high-performance ones) over the Internet, society at large now needs to be more aware of the danger posed by these devices, particularly to children and adolescents.